2020
DOI: 10.4314/aas.v17i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of gunshot abdominal injuries

Abstract: To describe prevalence, management and factors determining outcomes in patients presenting with gunshot abdominal injuries. Method: We retrospectively analysed all cases of gunshot to the abdomen received at Kenyatta National Hospital from October 2013 to October 2017. Patients' demographic and clinical data were collected from their case notes. Data analysis used Fisher's exact test and binary logistic regression. A p-value of <0.05 was considered statistically significant. Results: A total of 1,588 records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been well documented that the time from injury to surgery is an effective factor in the development or increase in the depth of shock. [ 16 ] In our study, it was observed that the time from injury to surgery had a significant effect on mortality (P<0.001) but had no significant effect on the development of complications.…”
Section: Discussionmentioning
confidence: 61%
“…It has been well documented that the time from injury to surgery is an effective factor in the development or increase in the depth of shock. [ 16 ] In our study, it was observed that the time from injury to surgery had a significant effect on mortality (P<0.001) but had no significant effect on the development of complications.…”
Section: Discussionmentioning
confidence: 61%
“…However, the variability in terms of how dangerous they provoke complications exist. For instance Gunshot as one of the mechanisms of penetrating abdominal injury is associated with many complications [1]. If the bullet of high velocity and large mass was used, many complications develop because of the damage of multiple abdominal organs.…”
Section: Mechanisms Of Abdominal Trauma Related Risk Factorsmentioning
confidence: 99%
“…Moreover, other authors have devised criteria of complication in surgical practice; in certain book of neurosurgery complication has been regarded as an occurrence which fulfills three criteria namely, unwanted, unplanned and does not commonly occur. Management of abdominal trauma is complex and remains a problematic in surgical practice due to notable occurrence of numerous complications [1]. Failure to recognize and treat these complications earlier increases the mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%